THE EFFECTIVENESS OF ONLINE LEARNING TOWARDS THE LEARNING RESULTS IN IPS SUBJECTS FOR CLASS VIII STUDENTS OF SMP NEGERI 20 BEKASI - Nada Afriyanisa (Jurnal Ilmu Pendidikan Ahlussunnah, 2022)
The aim of the study is to find out the effectiveness of online learning towards the learning results in IPS subjects for class VIII students of smp Negeri 20 Bekasi. The data collecting technique uses questionnaire and documentation. The sample is taken from the population of the eighth grade students of SMP Negeri 20 Bekasi. The sampling method uses the random sampling. The research method used is survey and quantitative approach and the data analyzing technique uses the application of SPSS 25.0. (1) The result of correlation indicates the score of 0,731 and The score of relation between online learning and the learning results of the cognitive, affective, as well as psycho-motor scores indicates -0,243.(2) The coefficient test indicates that the score of Adjusted R Square of the online learning variable (X) towards the learning results (Y) yields the score of 52,5% and The coefficient test indicates that the score of Adjusted R Square of the online learning variable (X) towards the learning results (Y) the learning results of the cognitive, affective and psycho-motor yields the score of 3,9%.